RADICAL SCAVENGING ACTIVITY OF LIGNIN EXTRACTED FROM OIL PALM EMPTY FRUIT BUNCH AND ITS EFFECT ON GLUTATHIONE-S-TRANSFERASE ENZYMES ACTIVITY - Mohd Salleh, Norliyana; Ismail, Sabariah; Mohamad Ibrahim, Mohamad Nasir (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Lignin consists of cell wall phenylpropanoid polymers widespread in all vascular plants and is present in lignocellulosic waste such as oil palm empty fruit bunch (OPEFB). The presence of valuable compounds in OPEFB lignin such as vanillin, syringaldehyde, and p-hydroxybenzaldehyde promise additional value to lignin especially in pharmaceutical and food supplement industries. Methods: In this study, lignin was isolated from OPEFB using three types of extraction techniques (soda, kraft, and organosolv)and characterized via calorimetric, chromatographic, and spectroscopic methods. The antioxidant activity of all three types of OPEFB lignin by 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical-scavenging effect was examined. OPEFB lignin extracts were therefore further investigated for their influence on glutathione-S- transferase enzymes activity in rat liver cytosolic fractions using spectrophotometer assay. Results: The kraft OPEFB lignin showed the highest DPPH free radical scavenging effect compared to the other. High-performance liquid chromatography analysis revealed that all OPEFB lignin were mainly formed by p-hydroxyphenyl (H) guaiacyl (G) and syringyl (S) units whereas vanillin and syringaldehyde were the main compounds in soda, kraft, and organosolv OPEFB lignin. Soda OPEFB lignin showed the most effective inhibition of rat liver cytosolic glutathione S-transferases activity toward 1-chloro-2,4-dinitrobenzene followed by kraft OPEFB lignin. Conclusion: This study found that the antioxidant activities of all three types of OPEFB lignin were related to the phenolic hydroxyl group (ArOH) contents and their Mw, Mn, and Mw/Mn values. The effect of OPEFB lignin on the inhibition of GST enzymes activity shows good correlation with the total flavonoid content of each OPEFB lignin. Keywords: Oil palm empty fruit bunch lignin, Antioxidant activity, Glutathione-S-transferase, Syringaldehyde, Vanillin.